Money Laundering in the Light of Financial Regulations - Jaszek, Tomasz (Journal of Finance and Financial Law, 2018)
The money laundering class falls under the category of economic crimes. The scale of this phenomenon is the subject of many discussions and deliberations on the international arena. World organizations such as the OECD or FATF undertake numerous initiatives against a real threat to the financial market. The effect of international cooperation is the development by the European Union of a significant legal regulation, recognized as the AML IV Directive, which Member States are obliged to introduce into the national legal order. The concept of EU regulation is to strengthen the cohesion and credibility of the Community financial sector. Also in Poland, legal and institutional solutions have been developed, the intention of which is to effectively and effectively combat the money laundering process. The purpose of this article is to review Polish regulatory solutions aimed at counteracting money laundering.